Sodium hydroxide treatment on natural fibers for better fiber morphology: A review / Nor Farhana Jasmi, Nur Farahin Yusoff and Jamaludin Kasim - Jasmi, Nor Farhana; Yusoff, Nur Farahin; Kasim, Jamaludin (2011)
Lignocellulosic fibers seem to be among the best alternative substitution fillers in biocomposite. Among its usages includes as particleboard (PB) and wood polymer composite (WPC) as it is abundantly available and its woody properties offers great usability. However, several problems arise due to the high hygroscopicity of woody materials and less interfacial adhesion between hydrophilic filler with hydrophobic petroleum based polymer. A variety of alkali treatments has been reported in the enhancement of promoting better fiber morphology and thus reduce the water uptake behavior and increase the compatibility. This paper intended to review the alkalization treatment using Sodium Hydroxide (NaOH) on natural fiber surfaces, differentiate treated and untreated fiber surfaces and summarize the effective concentration of NaOH which may be applied on certain wood species. The findings are hoped to be used as a guide throughout future researches.